2019
DOI: 10.1039/c9qo00561g
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative selenofunctionalization of allenes: convenient access to 2-(phenylselanyl)-but-2-enals and 4-oxo-3-(phenylselanyl)pent-2-enoates

Abstract: The controlled preparation of two types of α-seleno-α,β-unsaturated carbonyls, namely, α-selenoenals and α-selenoenones, have been accomplished.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…A gram-scale reaction between 1g and 2a delivered 1.0465 g of 3ga in 93% yield with a reduced loading of both the catalyst and ligand ( Scheme 2a ). As a class of synthetically useful chemicals, the versatile allenyl unit could be transferred into different structure units: selenohydroxylation and oxidation of 3ga with 1-fluoropyridinium/1,2-diphenyldiselane could deliver 2-selenoenal 4 with a Z / E selectivity of 94/6; 14 bromohydroxylation of this allenyl group in aqueous dioxane afforded terminal 2-bromoallylic alcohol 5 as the sole product in 72% yield; 15 the allenyl group may also be selectively transformed into the corresponding primary allylic alcohol 6 with an E / Z selectivity of 98/2 by a gold-catalyzed hydration reaction; 16 iodination of the allenyl group exclusively gave diiodide product ( Z )- 7 in 69% yield. 17 It should be noted that these products are difficult to synthesize through traditional transition-metal catalyzed coupling reactions.…”
Section: Resultsmentioning
confidence: 99%
“…A gram-scale reaction between 1g and 2a delivered 1.0465 g of 3ga in 93% yield with a reduced loading of both the catalyst and ligand ( Scheme 2a ). As a class of synthetically useful chemicals, the versatile allenyl unit could be transferred into different structure units: selenohydroxylation and oxidation of 3ga with 1-fluoropyridinium/1,2-diphenyldiselane could deliver 2-selenoenal 4 with a Z / E selectivity of 94/6; 14 bromohydroxylation of this allenyl group in aqueous dioxane afforded terminal 2-bromoallylic alcohol 5 as the sole product in 72% yield; 15 the allenyl group may also be selectively transformed into the corresponding primary allylic alcohol 6 with an E / Z selectivity of 98/2 by a gold-catalyzed hydration reaction; 16 iodination of the allenyl group exclusively gave diiodide product ( Z )- 7 in 69% yield. 17 It should be noted that these products are difficult to synthesize through traditional transition-metal catalyzed coupling reactions.…”
Section: Resultsmentioning
confidence: 99%
“…As per mechanistic pathway proposed by the authors, the reaction of both the substrates mediates through phenylseleniranium intermediates produced by selective attack of electrophilic species PhSe(OTf) on the alkenes as per the substrate followed by the regioselective attack of water and then final oxidation by 1‐fluoropyridinium reagent [126] …”
Section: Overview On Selenium‐catalyzed/selenium Incorporating Transfmentioning
confidence: 99%
“…Their enantioselectivity has been extended to conjugate addition of organometallic reagents to enones and palladiumcatalyzed stereoselective allylic alkylations. [34] In 2019, Benito et al, [126] reported regio and stereoselective organoselenium-mediated oxidative selenofunctionalization of allenes 60 to provide α-selenoenals 61 and α-selenoenones 62. The method utilizes the appealing reactivity of 1-Fluoropyridinium reagent towards oxidative functionalization reaction [16,127] and presence of water in the solvents used, plays a vital role in providing the carbaldehyde oxygen in 61 & 62 (Scheme 26).…”
Section: Organoselenium Reagents As Regioselective and Stereoselectivmentioning
confidence: 99%
See 1 more Smart Citation
“…In subsequent work, Alcaide and coworkers reported a metal-free oxidative selenofunctionalized reaction between allenes and diphenyl diselenide (Scheme 6). 14 Scheme 5 The selenocyclization of 2-indolinone-tethered allenols for the synthesis of spirocyclic selenolactams and quinoline-2,3-diones.…”
Section: Traditional Selenocyclizationmentioning
confidence: 99%